Uma argumentação em torno do suicídio - Lúcio Vaz de Oliveira (2014)
The thesis has, in general terms, a twofold purpose: to establish a taxonomy of the several arguments about suicide; to assess these arguments and present a critical position. In order to accomplish these two purposes, I try to work out a conceptual mapping of suicide andof possible approaches to the issue concerning the following question: could there be any rational choice for the suicide, from the practical point of view? The taxonomy presents three clusters resulting in practical attitudes: indifference, agreement or rejection. Since agreementand rejection involve different shadowings, we have four basic kinds of attitude toward suicide: indifference, unconditional acceptance, conditioned acceptance and unconditional rejection. These attitudes, in their turn, multiply themselves into various arguments and motivations.With regard to my critical assessment, I propose, on one hand, a moral deontologically inspired argument, on the other, one grounded on a practical field not guided by morality, a field that is existential and prudential. The conclusion affirms that suicide can be consideredacceptable at different levels of rationality, such as with regard to consistency between actions and beliefs and between premises and conclusions. However, suicide cannot be rational at the most rigorous levels of practical rationality, either moral or prudential, because this level also is related to the acceptability of assumptions and beliefs. Some assumptions that are unfolded and defended throughout the thesis contribute for this unconditionally negative evaluation of suicide. I could refer among others to a claim of intentionality that incorporates the acceptance of the foreseeable consequences of the action; to a conception of identity centered on the intention of future psychological continuity; to a preference for the individual regard about himself and not for his image before other people's eyes.